Recalcitrant Reactive Perforating Collagenosis Successfully Treated with Dupilumab: A Case Report [Corrigendum] - Li J; Zhou C (Dove Medical Press, 2024)
Li J, Zhou C. Clin Cosmet Investig Dermatol. 2024;17:1329–1332. The authors have advised that they neglected to include a funding statement on page 1331 of the published paper. The funding statement should read as follows. FundingThis study was supported by the National Natural Science Foundation of China (No.82073459, No.82373504). The authors apologize for this error.